2017
DOI: 10.1128/jvi.00237-17
|View full text |Cite
|
Sign up to set email alerts
|

Hili Inhibits HIV Replication in Activated T Cells

Abstract: P-element-induced wimpy-like (Piwil) proteins restrict the replication of mobile genetic elements in the germ line. They are also expressed in many transformed cell lines. In this study, we discovered that the human Piwil 2 (Hili) protein can also inhibit HIV replication, especially in activated CD4+ T cells that are the preferred target cells for this virus in the infected host. Although resting cells did not express Hili, its expression was rapidly induced following T cell activation. In these cells and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…It has been reported that the expression of HERV‐R was significantly upregulated by treatment with tumor necrosis factor‐α, interleukin (IL)‐1α, and IL‐1β and downregulated by treatment with interferon (IFN)‐γ . The important role for small RNAs (such as Piwi‐interacting small RNA) in silencing ERVs via homology‐dependent mechanisms has been confirmed in mouse . However, the role of small RNAs in regulating the expression of HERVs in human needs further investigation.…”
Section: Regulatory Mechanisms Of Herv Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the expression of HERV‐R was significantly upregulated by treatment with tumor necrosis factor‐α, interleukin (IL)‐1α, and IL‐1β and downregulated by treatment with interferon (IFN)‐γ . The important role for small RNAs (such as Piwi‐interacting small RNA) in silencing ERVs via homology‐dependent mechanisms has been confirmed in mouse . However, the role of small RNAs in regulating the expression of HERVs in human needs further investigation.…”
Section: Regulatory Mechanisms Of Herv Expressionmentioning
confidence: 99%
“…70 The important role for small RNAs (such as Piwi-interacting small RNA) in silencing ERVs via homology-dependent mechanisms has been confirmed in mouse. 73,83 However, the role of small RNAs in regulating the expression of HERVs in human needs further investigation.…”
Section: Activation Of Hervs By Host Factorsmentioning
confidence: 99%
“…Codon usage of viral genes was reflected by the changes in polysome-associated tRNA levels, which implied the existence of local tRNA pools optimized for viral translation. 64 To demonstrate this, the researchers used an antisense oligonucleotide to specifically deplete tRNA Arg (UCU) in target cells, which inhibited HIV replication. 59 Under the catalysis of reverse transcriptase (RT), the host tRNA Lys 3 , which served as a reverse transcription primer for HIV-1, bound to the viral genomic RNA to initiate reverse transcription.…”
Section: Trnas and Immune Responsesmentioning
confidence: 99%
“…Peterlin et al discovered that P-element-induced wimpy-like 2 (Hili) protein inhibited HIV replication by binding to rare tRNAs such as tRNA Arg(UCU) and tRNA Ile(UAU) in activated CD4 + T cells. 64 To demonstrate this, the researchers used an antisense oligonucleotide to specifically deplete tRNA Arg (UCU) in target cells, which inhibited HIV replication.…”
Section: Trnas and Immune Responsesmentioning
confidence: 99%
“…To gain insight into the mechanism by which Vpx overcomes transcriptional silencing of lentiviral transgenes, a loss-of-function screen was performed focusing on genes reported to contribute to silencing of retroviruses and other transcriptional targets (Chéné et al, 2007; Peterlin et al, 2017; Tchasovnikarova et al, 2015, 2017; Wang and Goff, 2017; Weinberg and Morris, 2016; Wolf and Goff, 2007). Jurkat T cells were transduced with lentivectors that confer puromycin resistance and express shRNAs (Pertel et al, 2011b) targeting either AGO1, AGO2, AGO3, DNMT3A, HDAC1, HP1, SUV39H1, SUV39H2, PIWIL2, TRIM28, SETDB1, FAM208A, MPHOSPH8, PPHLN1, or MORC2.…”
mentioning
confidence: 99%